Optimizing the Role of Curriculum Leaders in Enhancing English Language Teaching Quality - Hensi Nurhayati; Rambar Nur Sasongko; Connie Connie (PPSDP International Journal of Education, 2026)
This study aims to describe the optimization of curriculum leadership roles in improving the quality of English language teaching, focusing on the contributions of principals, vice principals, teachers, MGMP, and supervisors in curriculum management. The study emphasizes how these roles collectively influence the effectiveness of English learning in junior high schools. A descriptive qualitative design was employed, with data collected through semi-structured interviews, classroom and institutional observations, and document analysis. The participants consisted of one principal, one vice principal for curriculum affairs, and four English teachers at SMPN 11 Bengkulu City. Data were analyzed using Miles and Huberman’s interactive model, involving data reduction, data display, and conclusion drawing. The findings revealed that school leaders and teachers focus more on administrative tasks than improving teaching. As a result, students remain passive learners, developing stronger academic skills than practical abilities. This study highlights a systemic culture of administrative compliance that constrains instructional leadership in English language education. Unlike much of the existing literature that focuses on curriculum design, this study addresses the overlooked dimension of curriculum implementation and management at the school level. The study proposes the development of an “Integrated Curriculum Leadership” model in which principals, vice principals, MGMP, and supervisors collaborate synergistically to foster instructional innovation, teacher professional growth, and student communicative competence. By mapping existing practices, identifying gaps, and proposing a collaborative framework, this study contributes both theoretically and practically to the discourse on curriculum leadership. It underscores the need for school leaders and policymakers to move beyond managerialism and create conditions that support sustainable, pedagogically oriented curriculum implementation for English learning.